Caring Behavior Improvement Model on Nursing Students at Poltekkes Kemenkes Pangkalpinang - Nurhayati Nurhayati (Journal of Global Pharma Technology, 2020)
This study aims to establish models and measures of caring behavior in nursing students at the Poltekkes Kemenkes Pangkalpinang. The research method used is a quantitative method with survey techniques in phase I, and experiments by making a book as an experimental tool with the design of the One Group Pre-test Post-test for stage II. Furthermore, the data analyzed by qualitative methods in stage III. The sample consisted of 69 students; as a combination of first-year and second-year students. This study revealed that the Compassion variable influenced the formation of Competence, whereas the Conscience and Commitment variables did not affect the formation of Competency. Meanwhile, overall, the variable Compassion, Conscience, Commitment, and Competence influence the formation of Caring Behavior. Keywords: Behavior, Caring, Nursing, Students